Brahma Kamal (Saussurea obvallata (DC.) Edgew.): Ethnomedicinal, phytochemical and pharmacological overview of an important Himalayan medicinal plant - Semwal, Prabhakar; Painuli, Sakshi; Tewari, Devesh; Bussmann, Rainer W; Palni, Lok Man S; Thapliyal, Ashish (Ethnobotany Research and Applications, 2020)
Background: The genus Saussurea of Asteraceae comprises approximately 490 species. Plants belonging to this genus are being used in different countries as traditional medicines. Brahma Kamal (Saussurea obvallata (DC.) Edgew.), is one of the most important and endangered species of this genus and is being used in traditional, ornamental and religious purposes. The aim of this work is to review and understand the scientific work conducted so far on S. obvallata, which includes its ethnomedicinal uses, pharmacognostic description, phytochemistry, pharmacology, micro-propagation and important conservation aspect. Methods: Systematic literature searches were performed on S. obvallata through various scientific search engines including Google Scholar, Scopus, PubMed, USPTO, Agricola, Science Direct, Mendely, Springer, JSTOR, Research Gate, Google patents, published books and conference proceedings using different keywords for screening of relevant information. Results & Conclusion: The literature analysis revealed diverse traditional uses of S. obvallata, against wounds, paralysis, cerebral-ischemia, cardiac and mental disorders. Various extracts of S. obvallata were also evaluated for their chemical composition and pharmacological activities including but not limited to anti-hypoxia, anticancer, radio-protective, antioxidant and antimicrobial activities using different in-vitro and in-vivo models. S. obvallata is being used widely in traditional medicine and socio-economic applications but scientifically, it is not fully assessed regarding its complete therapeutic effects, toxicity and safety in human body. Further studies are essential and also should focus on the conservation, cultivation and sustainable utilization of the species.